Surgical correction of distal tibia posttraumatic deflection - Trufanov, I. I.; Pobiel, Ye. A.; Kosylo, V. V. (Zaporozhye Medical Journal, 2018)
Objective – to study the issues related to diagnostics and treatment of pilon fracture of the tibial epiphysis and individual approach to surgical correction of posttraumatic deformations of the distal tibia. Material and methods. The treatment results of 49 patients who had suffered pilon fractures throughout 1–2 years after treatment completion were studied in the clinic of Traumatology and Orthopedic on the basis of “ZSMKH №9”. According to the AO classification patients had the following types of fractures: 43A – 7 patients, 43B – 14 and43C – 28. The X-ray measurements characterizing the geometric shape of articular surfaces were measured. The mathematical finite element method of computer modeling was used for the study of bone and cartilaginous tissues stress distribution pattern in the ankle joint in its normal condition and in case of post-traumatic deflections. Results. The basic pathological symptom in patients with pilon fractures of distal tibia is joint function limitation, which spreads to the sector of dorsal extension, regardless of the pilon fracture type. The joint continues to function, however movement amplitude is decreased. The most unfavorable change of distal tibia shape is valgus inclination of articular surface. This configuration change of tibial articular end requires repeated surgical correction. Conclusions. The main task of the distal tibial epiphysis surgical correction is the weight-bearing function and axial relationships restoration and pain management. It can be concluded that selective approach to posttraumatic deformations of the distal tibia surgical correction is essential. The main indications for surgical correction are pseudarthrosis, deviations in the frontal plane of more than 10 degrees, severe joint arthrosis accompanied by pain syndrome for more than a year.